Analisis Pengaruh Pengujian Tekan Terhadap Suhu, Pengeringan Awal, Suhu dan lama Penahanan Waktu Pemanasan Bata Merah - Yuliyanto Yuliyanto; Eko Yudo; Ramli Ramli (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Red brick is a very important building material in building construction. Red brick has a rectangular physical shape with a distinctive color, namely red. Red bricks are made of clay mixed with sand and water, then mixed evenly and molded as desired. According to the quality standards, red brick is said to be of good quality and quality if it has several criteria including having the required size, compressive strength, and water absorption capacity. This research was conducted to see the effect of the length of drying time after printing, the effect of heating time, heating temperature, and the surface topography of red brick. The data processing method uses the Response Surface (RSM) method using Design Expert 09 software. The results show the smallest compressive test value of 131.4 kg/cm2. The biggest value is 148 kg/cm2. The most significant influence on the red brick making process is the drying time. The longer the drying process will cause the water content in the red brick to decrease. The SEM results show that the effect of drying red bricks that experience longer drying will coalesce and crystallize more easily. Based on the analysis of the results of the study that a longer drying time will cause an increase in compressive strength.